Our Spiritual Relations: Challenging Settler Colonial Possessiveness of Indigenous Spirituality/Religion - Gareau, Paul; LeBlanc, Jeanine (Anthropologica, 2023)
Indigenous spirituality is often appropriated and deployed in support of white settler values that possess and dispossess Indigenous knowledges, materiality, and socio-political relations. As Kim TallBear explains, this settler property regime maintains a colonial exceptionalism that justifies settler naturalization to Indigenous territories. Indigenous spirituality/religion represents situated knowledges and socio-political relations that cannot be abstracted from collective and co-constitutive relations. LeBlanc and Gareau turn to their respective communities to articulate how relations are central to understanding Indigenous spirituality/religion. LeBlanc employs Savage (Tracy) Bear’s eroticanalysis to see Mi’kmaq women’s spiritual/religious relations in the settler archives as well as situate herself in these relations through photographic self-portraiture. Gareau unpacks the spiritual/religious relations of the Métis fiddle in Maria Campbell’s Road Allowance story of “La Beau Sha Shoo” where a Métis fiddler dies and goes to heaven to drink and visit with Jesus. Throughout, spirituality/religion represents the self- determination of separate but related collective and co-constitutive nations/ peoples.